Awareness of Cervical Cancer Screening test Among Women of Child Bearing age in the Rural Area of Awo-Omamma, Imo State, Nigeria. - Martin.C, Ezeama,; , Enwereji,E.E (International Journal of Health Statistics, 2020)
Introduction This study assessed the awareness of cervical cancer screening test among women in the rural area of Imo State. Cervical cancer is the fourth most common cancer and the cause of death in women. The need to ascertain the level of awareness of cervical cancer screening test and the level of uptake among rural women motivated this study. Materials and Methods The study design was cross sectional descriptive survey. The sample for the study, which was statistically determined by Taro Yamane formula was 420. Administered structured questionnaire was used for data collection. Data were analyzed using frequency distribution tables. Results The result showed that 270(64.3%) of the respondents were aware of cervical cancer screening test and only 135(32.1%) used cervical cancer screening test . Majority of the respondents, 400(95.2%) have never taken vaccination for human papilloma virus . The main place where 234(55.7%) of the respondents learnt about cervical cancer screening was the hospital. A good number of the respondents 225(53.6%), had low uptake services because of the views that cervical cancer screening is mainly for the elderly women, and also 140(33.3%) felt that the investigation process is painful. Conclusion Therefore, adequate and substantial measures should be taken to health educate women on benefits of cervical cancer screening tests.
Keywords: Cervical Cancer; Screening test; Women; mobilization